Trust‐based security‐level evaluation method for dynamic service‐oriented environments. (27th July 2015) - Kołaczek, Grzegorz; Juszczyszyn, Krzysztof; Świątek, Paweł; Grzech, Adam; Schauer, Patryk; Stelmach, Paweł; Falas, Łukasz
Summary: A method of decision‐making in security‐level estimation process of service‐based applications in future Internet architecture is proposed. We demonstrate how distributed services can be composed to form an application run within the next‐generation network infrastructure and their security level may be assessed. Our approach is illustrated by the experiments carried on exemplary application (virtual laboratory online lab, using future Internet IPv6 QoS architecture), in which our method was evaluated against two types of attacks observed with the use of traffic anomaly detection methods. Copyright © 2015 John Wiley & Sons, Ltd.